Pandawa Seraja (Pramuka Mawas Bencana Sehat Raga dan Jiwa) in SMP Negeri 2 Martapura Timur Banjar Regency - Neka Erlyani; Vina Yulia Anhar; Ihya Hazairin Noor; Zuhrufa Wanna Yolanda; Devi Damayanti; Nuraida Nuraida (Jurnal Berkala Kesehatan, 2023)
Floods are the most frequent disasters globally and cause significant impacts and losses. One of the impacts is psychological impact in the form of fear and anxiety. One-third of the victims were children which can result in psychological "trauma" to victims.East Martapura District is one of seven sub-districts in Banjar Regency which is often affected by flooding.Know that 47 adolescents aged 15-24 years in Banjar Regency were directly affected by the 2021 floods.This activity aims to reduce negative impacts such as stress, depression and others.This activity begins with flood education games by telling experiences or things that are known about flooding, delivering educational videos about flooding and flood preparedness, education about "The Importance of Mental Health During Floods". And finally, students are invited to color the prepared pictures using colored pencils. Evaluation of activities was carried out using a pre-post test.The results of the evaluation showed an increase in knowledge of 83.33%. Apart from that, the psychological assistance provided aims to provide mental readiness for SMPN 2 Martapura scout members to face challenges. Thus, this service not only enriches knowledge, but also helps in developing the physical and mental well-being of active scout participants at SMPN 2 Martapura Timur.